Digestibility of pumpkin by-products as a promising raw material in the technology of bakery products - Shevchenko, Anastasiia (My University, 2024)
Pumpkin seed flour and pumpkin protein concentrate were used for research. Protein digestibility was determined in vitro, using the enzymes pepsin and trypsin, for 3 hours and compared with the digestibility of high-grade wheat flour proteins. It was established that the protein digestibility of pumpkin seed flour was 4.02% abs., and pumpkin protein concentrate – 43.31% abs. The high in vitro digestibility of pumpkin protein is associated with a lower fiber content compared to flours. Thus, the use of pumpkin by-products in the recipe of wheat bread will increase the digestibility of protein substances by the body.

Для досліджень використовували борошно з насіння гарбуза та білковий концентрат гарбуза. Перетравність білка визначали in vitro з використанням ферментів пепсин і трипсин протягом 3 годин і порівнювали з перетравністю білків пшеничного борошна вищого сорту. Встановлено, що перетравність білка борошна з насіння гарбуза становила 4,02% абс., ​​а білкового концентрату гарбуза – 43,31% абс. Висока засвоюваність білка гарбуза in vitro пов’язана з меншим вмістом клітковини порівняно з борошном. Таким чином, використання субпродуктів гарбуза в рецепті пшеничного хліба підвищить засвоюваність білкових речовин організмом.
Keywords: dough; pumpkin seed flour; pumpkin protein concentrate; digestibility; wheat flour; кафедра технології хлібопекарських і кондитерських виробів; тісто; борошно з насіння гарбуза; білковий концентрат гарбуза; засвоюваність; борошно пшеничне